2010
DOI: 10.3389/fnhum.2010.00063
|View full text |Cite
|
Sign up to set email alerts
|

Spatial probability aids visual stimulus discrimination

Abstract: We investigated whether the statistical predictability of a target's location would influence how quickly and accurately it was classified. Recent results have suggested that spatial probability can be a cue for the allocation of attention in visual search. One explanation for probability cuing is spatial repetition priming. In our two experiments we used probability distributions that were continuous across the display rather than relying on a few arbitrary screen locations. This produced fewer spatial repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
108
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 38 publications
(65 reference statements)
7
108
0
Order By: Relevance
“…Whereas most studies use a handful of cue and target locations, making even uninformative cues somewhat reliable, the likelihood of the target appearing at the cued location in our study was low: 1/121, to be exact (or a 25/121 likelihood of appearing in the cued quadrant). It is reasonable to suppose that the unreliability of the cue affected the distribution of attention (e.g., Druker & Anderson, 2010). However, even though the likelihood of the target appearing at the cued location was very low (1/121), we still replicated the typical facilitation-then-inhibition crossover pattern at the cued versus the opposite location (see Fig.…”
Section: Discussionmentioning
confidence: 50%
“…Whereas most studies use a handful of cue and target locations, making even uninformative cues somewhat reliable, the likelihood of the target appearing at the cued location in our study was low: 1/121, to be exact (or a 25/121 likelihood of appearing in the cued quadrant). It is reasonable to suppose that the unreliability of the cue affected the distribution of attention (e.g., Druker & Anderson, 2010). However, even though the likelihood of the target appearing at the cued location was very low (1/121), we still replicated the typical facilitation-then-inhibition crossover pattern at the cued versus the opposite location (see Fig.…”
Section: Discussionmentioning
confidence: 50%
“…Unbeknownst to participants, across multiple trials, the T target is more often found in a highprobability, ''rich'' quadrant than in the other ''sparse'' quadrants. Previous research has shown that participants rapidly acquire a spatial bias toward the rich quadrant (Druker & Anderson, 2010;Geng & Behrmann, 2002;Umemoto, Scolari, Vogel, & Awh, 2010). In addition, this spatial bias persists for several hundred trials of extinction training (Jiang, Swallow, Rosenbaum, et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…However, some researchers have posited a longer-term role for spatial priming, specifically claiming that it forms the building blocks of probability cueing (Walthew & Gilchrist, 2006), in which stable locations of interest in the environment gain prolonged prioritization. If Walthew and Gilchrist are correct (but see Druker & Anderson, 2010;Geng & Behrmann, 2005;Jiang, Swallow, Rosenbaum & Herzig, 2013, for debate on this point), it is plausible that the purpose of spatial priming is to constantly increment spatial priority at recent locations of interest in space, ultimately producing the long-term biases when spatial statistical regularities are present. This idea is consistent with instance-based theories of learning (Logan, 1988), in which learning becomes stronger over time because with each instance a separate memory trace is laid down that can be recruited at retrieval.…”
Section: If Priming Is Adaptive Why Isn't It Optimal?mentioning
confidence: 99%